Ks. Józef Grzywaczewski, The Biblical Idea of Divine Mercy in the Early Church, Warszawa: Wydawnictwo Naukowe Uniwersytetu Kardynała Stefana Wyszyńskiego 2016, 378 s. - Sakowicz, Eugeniusz (Studia Nauk Teologicznych PAN, 2020)
Nie wymagany